Arterial blood gas analysis predicts futile recanalization in mechanical thrombectomytreated acute ischemic stroke patients: A multicenter study - Onalan, A.; Gurkas, E.; Akpinar, C.K.; Dogan, H.; Acar, T.; Acar, B.; Ozdemir, A.O. (Verduci Editore s.r.l, 2024)
OBJECTIVE: It is known that providing recanalization alone in large vessel occlusions is not sufficient to provide a good 90-day clinical outcome. It is advocated that neuroprotection should be increased before endovascular treatment and that the penumbra should be protected from reperfusion damage after recanalization. However, the effects of blood gas parameters before and after mechanical thrombectomy on clinical outcomes are not clear. The objective of this study is to assess the effectiveness of serial blood gas measures in accurately predicting futile recanalization at an early stage. PATIENTS AND METHODS: This study is a multicenter inquiry that collected data in a prospective manner and analyzed it retrospectively. Patients with a 2b-3 thrombolysis in cerebral infarction (TICI) score after mechanical thrombectomy for recanalization were consecutively analyzed from July 2022 to March 2023. Arterial blood gas parameters, including pH, oxygen saturation (SaO2), partial carbon dioxide pressure (PaCO2), partial oxygen pressure (PaO2), lactate, and bicarbonate (HCO3), were measured at four time points: before mechanical thrombectomy treatment (preoperative), immediately after recanalization (postoperative 1st), during the 3rd hour (postoperative 3rd), and at the 5th hour (postoperative 5th). The patients were categorized into groups based on their modified Rankin Scale (mRS) scores. RESULTS: The study included 136 patients with an average age of 69.71 11.22. The postoperative 1st-hour SaO2 values were lower in the mRS 3-6 group (p=0.038). The postoperative pH and lactate mean were greater in the mRS 3-6 group than in the 0-2 group (p=0.038 and 0.018, respectively). In logistic regression, a unit rise in lactate increased poor functional outcomes 1,632 times (p=0.024). Early neurological recovery was associated with decreased postoperative 3rd-hour lactate (p=0.014). The mean postoperative PaO2 (average of 1, 2, 3 PaO2) was higher in those with symptomatic cerebral bleeding (p=0.044). CONCLUSIONS: Monitoring lactate and pH levels in AIS patients who have had mechanical recanalization can be utilized to predict mortality and morbidity, especially in the first five hours after the procedure. © 2024 Verduci Editore s.r.l. All rights reserved.
Keywords: Blood gas analysis; Hyperoxia; Intracranial hemorrhage; Lactate; Oxygen saturation; Thrombectomy